The Role of Husband in Forming a Household Harmonious According to the Sunnah of the Prophet Muhammad SAW - Nasywa Nabilah Nugroho; Ahmad Zuhri Rangkuti (LEGAL BRIEF, 2026)
This study aims to examine the role of husbands in forming harmonious families according to the sunnah of the Prophet Muhammad SAW. This type of research is Library Research, which is an activity that includes selecting research theories, identifying literature and applying the results of the analysis as a theoretical basis, this study focuses on literature by analyzing the contents of the literature related to research from both primary and secondary sources. The data collection technique used is literature data collection. For the data analysis techniques used in this study are deductive, inductive and comparative methods. The results of this study indicate that the household life of the Prophet Muhammad SAW was full of affection, appreciation, and wisdom, forming and fostering a family that could be an ideal example for today's Muslim families. Likewise, in solving family problems, the Prophet Muhammad SAW used wise methods such as joking and joking, letting problems go for a while, giving advice and teaching and giving reprimands that could solve the problems of the Prophet Muhammad SAW with his wives. These principles are very relevant and can be applied to today's families to help create a harmonious family.